A Sulfur–Limonene‐Based Electrode for Lithium–Sulfur Batteries: High‐Performance by Self‐Protection. Issue 13 (14th February 2018) - Wu, Feixiang; Chen, Shuangqiang; Srot, Vesna; Huang, Yuanye; Sinha, Shyam Kanta; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract: The lithium–sulfur battery is considered as one of the most promising energy storage systems and has received enormous attentions due to its high energy density and low cost. However, polysulfide dissolution and the resulting shuttle effects hinder its practical application unless very costly solutions are considered. Herein, a sulfur‐rich polymer termed sulfur–limonene polysulfide is proposed as powerful electroactive material that uniquely combines decisive advantages and leads out of this dilemma. It is amenable to a large‐scale synthesis by the abundant, inexpensive, and environmentally benign raw materials sulfur and limonene (from orange and lemon peels). Moreover, owing to self‐protection and confinement of lithium sulfide and sulfur, detrimental dissolution and shuttle effects are successfully avoided. The sulfur–limonene‐based electrodes (without elaborate synthesis or surface modification) exhibit excellent electrochemical performances characterized by high discharge capacities (≈1000 mA h g −1 at C/2) and remarkable cycle stability (average fading rate as low as 0.008% per cycle during 300 cycles). Abstract : A sulfur–limonene‐based cathode material is produced by large‐scale synthesis using the abundant, inexpensive, and environmentally benign raw materials sulfur and limonene. Owing to self‐protection and confinement of lithium sulfide and sulfur, detrimental dissolution and shuttle effects are successfully avoided. As a result, the sulfur–limonene‐based electrodes exhibit excellent electrochemical performances and remarkable cycle stability.